2016
DOI: 10.5935/1806-6690.20160034
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of maize withAzospirillum brasilensein the seed furrow

Abstract: -Several studies addressing the inoculation of cereals with diazotrophic microorganisms can be found in the literature. However, in many experiments, investigators have overlooked the feasibility of applying these microorganisms to the furrow together with the seed, and the effect of bacterial concentration on phytostimulation. The aim of this work was to evaluate the effect of doses of an inoculant based on Azospirillum brasilense, applied to the seed furrow when planting maize, combined with different doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 23 publications
(26 reference statements)
2
23
0
8
Order By: Relevance
“…In this regard, while in Biari et al (2008), Costa et al (2015) and Morais et al (2016) found an increase in seed weigh of maize after inoculation; on the other hand, no significant interaction between inoculation and seed weigh was reported by Novakowiski et al (2011). Also, Dobbelaere et al (1999) reported that inoculations with A. brasilense did not impact GNC in maize.…”
Section: Thousand Seed Weight (Tsw) and Grain N Content (Gnc)mentioning
confidence: 80%
“…In this regard, while in Biari et al (2008), Costa et al (2015) and Morais et al (2016) found an increase in seed weigh of maize after inoculation; on the other hand, no significant interaction between inoculation and seed weigh was reported by Novakowiski et al (2011). Also, Dobbelaere et al (1999) reported that inoculations with A. brasilense did not impact GNC in maize.…”
Section: Thousand Seed Weight (Tsw) and Grain N Content (Gnc)mentioning
confidence: 80%
“…In this regard, while in Biari et al (2008), Braccini et al (2012), Costa et al (2015) and Morais et al (2016) found an increase in seed weigh of maize after plant inoculation combined to N fertilizer rates, on the other hand, in Novakowiski et al (2011) there was no significant interaction between N levels and inoculation for TSW. However, while the later authors used the bacteria strain Sp245, Hungria et al (2010) pointed out that only the strains AbV4, AbV5, AbV6 and AbV7 are the most effective for maize.…”
Section: Thousand Seed Weight (Tsw)mentioning
confidence: 88%
“…Em outros trabalhos, contudo, a fixação biológica consegue suprir apenas parte do N necessário (KUKAMI et al, 2016), sendo a adubação nitrogenada indispensável para a obtenção de bons resultados (Morais et al, 2016). Além disso, há casos onde a simples inoculação permite a obtenção de bons rendimentos ou de ganhos em crescimento das culturas (GARCÍA-OLIVERAS, 2012;BRUM et al, 2016;MARTINEZ et al, 2016).…”
Section: Introductionunclassified